Pengaruh financial knowledege, financial behaviour, dan financial attitude terhadap keputusan berinvestasi pada masyarakat milenial - Ezra Edom Mangara; Maulana Malik Muhammad; Donant Alananto Iskandar (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This research aims to analyze the influence of Financial Behavior, attitudes, and knowledge on financial decision-making. The study utilized a sample of 100 individuals from the millennial population in Jakarta, with data collected through questionnaires representing primary data. SPSS Version 27 software was employed to conduct multiple linear regression analysis and hypothesis testing. The results indicate that the financial decisions made by millennials in Jakarta are positively influenced by their Financial Behavior, attitudes, and knowledge.